Sistem Pendidikan Islam Tradisional (Pesantren) Melalui Kurikulum Sains dan Teknologi: Manfaat, Tantangan, dan Resistensi: Penelitian - Asharo, Sukaina; Rina Setyaningsih; Hani Ah Hisyam, Ulfi; Habibi, Sayyid; Aziz Iskandar, Walid; Ulfa Nurjanah, Siti; Supadi, Ari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The modernization of traditional Islamic education systems, particularly pesantren, has become a significant phenomenon in responding to the development of science and technology in the era of globalization. This study aims to analyze the integration of science and technology curricula within the pesantren education system, focusing on its benefits, challenges, and forms of resistance. The research employs a literature review method, examining various studies, previous research findings, and curriculum documents from both modern and traditional pesantren. The findings indicate that the integration of science and technology provides significant benefits, including enhancing students’ competitiveness, expanding 21st-century competencies, and strengthening the relevance of pesantren amid changing times. However, this modernization process faces several challenges, such as limited human resources, resistance from some groups concerned about the loss of classical pesantren scholarly identity, and infrastructural constraints. Resistance also emerges in the form of selective attitudes by kyai regarding the inclusion of science and technology content to ensure alignment with Islamic values.